Salary and Job Axpectations of Generation Z Sebagai Pijakan Perusahaan dalam Penarikan dan Seleksi Talent. - Bambang Septiawan; Suprianto Suprianto (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2022)
The purposes of this study are firstly to find out the salary expectations that gen z want while working. Secondly, to analyze what types of jobs are interested in gen z. Finally, to describe how the strategies are applied by Gen Z to achieve the salary and work they want and the implications of this research for the company. The method used in this research is qualitative with a case study approach and quantitative with a survey approach. The sample used in this research is 108 students of the management department UNISBA Blitar belonging to gene z. Data collection techniques were carried out using questionnaires and structured interviews online. Analysis of the data used by describing the results of the numbers from the survey conducted then elaborated with the results of interviews and theories that have been written. The results of this study suggest that gen z wants a salary above 5 million with a percentage of 44.9% and the rest below 5 million. Furthermore, 39.6% want to be entrepreneurs for future types of work and the rest as employees of BUMN, ASN and others. In addition, they also carry out special strategies and tips to achieve what they expect.